On land - Biggs, Brian (Balzer + Bray, 2011)
A young boy learns about land vehicles from bicycles to subways and trolleys as he and his father travel to the train station
Keywords: Vehicles / Juvenile fiction; Vehicles / Fiction; Automobiles / Fiction